2009
DOI: 10.1523/jneurosci.5038-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Firing Patterns in Superior Colliculus of Head-Unrestrained Monkey during Normal and Perturbed Gaze Saccades Reveal Short-Latency Feedback and a Sluggish Rostral Shift in Activity

Abstract: The superior colliculus (SC) encodes a saccade via the spatial position of an ensemble of active neurons on its motor map. Downstream circuits control muscles with the temporal code of firing frequency and duration. The moving hill hypothesis resolves the SC-tobrainstem spatiotemporal transformation (STT) enigma by proposing feedback to the SC which "pushes" a hill of activity (height ϭ frequency) caudorostrally such that its instantaneous position encodes the angular error [gaze-position error (GPE)] between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 47 publications
(102 reference statements)
2
26
1
Order By: Relevance
“…Head-restrained studies that dissociated target location from gaze kinematics by varying initial eye position (Sparks and Mays, 1980) or perturbing eye muscles have suggested that SC neurons correlate best to the former, rather than the latter. However, it has often been argued that "freeing" the head reveals a more natural spatial coding in areas like the SC (Guitton, 1992;Paré and Munoz, 2001;Klier et al, 2003;Choi and Guitton, 2009). Nevertheless, the current study also suggests that the saccade-related burst in SC activity primarily encodes visual target direction during head-unrestrained gaze shifts, despite considerable variations in eye/head kinematics.…”
Section: Target Versus Gaze Movement Codingcontrasting
confidence: 44%
See 1 more Smart Citation
“…Head-restrained studies that dissociated target location from gaze kinematics by varying initial eye position (Sparks and Mays, 1980) or perturbing eye muscles have suggested that SC neurons correlate best to the former, rather than the latter. However, it has often been argued that "freeing" the head reveals a more natural spatial coding in areas like the SC (Guitton, 1992;Paré and Munoz, 2001;Klier et al, 2003;Choi and Guitton, 2009). Nevertheless, the current study also suggests that the saccade-related burst in SC activity primarily encodes visual target direction during head-unrestrained gaze shifts, despite considerable variations in eye/head kinematics.…”
Section: Target Versus Gaze Movement Codingcontrasting
confidence: 44%
“…The SC is involved in saccades and gaze control (Mays and Sparks, 1980b;Hepp et al, 1993;Tweed et al, 1998;Choi and Guitton, 2009), but it could either encode gaze kinematics (Sparks and Mays, 1980) or target information (Klier et al, 2001). Investigations of saccade dynamics during SC stimulation and recordings have suggested that the SC does influence velocity (Waitzman et al, 1991;Guitton, 1992;Van Opstal et al, 1995;Munoz et al, 1996).…”
Section: Target Versus Gaze Movement Codingmentioning
confidence: 99%
“…Finally, gaze, eye or head commands must be defined in some frame of reference (Crawford et al ., ). Some early studies suggested that space‐fixed goals are encoded in the posterior SC (Guitton et al ., ; Roucoux et al ., ; McIlwain, ), but since then most head‐unrestrained studies (Sparks, , ; Van Opstal et al ., ; Lee & Groh, ) and head‐unrestrained studies (Freedman & Sparks, ,b; Klier et al ., ; Choi & Guitton, ; DeSouza et al ., ) have emphasized eye‐centred codes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies have highlighted gaze shifts in which eye velocity exhibits a plateau toward the end of large gaze shifts (see, for example, Fig. 1A in Choi and Guitton 2009). Simulations by Galiana and colleagues (1992) suggest that, during the plateau phase, burst neurons continue to discharge albeit with an attenuated firing pattern; to our knowledge, electrophysiological recordings of BNs during such movements do not exist in literature.…”
Section: Template Matching and Attenuation Ratiomentioning
confidence: 99%